The translational potential of inflammation-induced skin blister human models in exploring the pathogenesis of periodontitis and its systemic health implications - Irwandi, Rizky Aditya; Marruganti, Crystal; Collins, George; Carvalho, Jhonatan de Souza; Gilroy, Derek; D’Aiuto, Francesco (Frontiers in Immunology, 2024)
Periodontitis is a highly prevalent chronic disease. Despite decades of extensive research on the topic, a complete understanding of its immunopathogenesis, especially when linked to other inflammatory comorbidities, is lacking. Ex vivo human and in vivo animal experiments have shown the host inflammatory response’s crucial role in both the disease’s onset and its systemic implications. These approaches, however, remain questionable when translating these findings into real-world scenarios linked to periodontitis. A clear need for new in vivo human models is discussed, especially within the context of understanding the host response to key pathogens linked to periodontitis, such as Porphyromonas gingivalis (P. gingivalis). Therefore, a skin blister model was employed to describe the stages of the host immune response in humans after challenges by microbial and/or sterile insults. A novel human challenge model using UV-killed P. gingivalis holds promise in producing new evidence and bridging the gap of the host response to periodontitis and its links with other common chronic diseases.